2018
DOI: 10.1016/j.jamcollsurg.2018.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Comanagement by Hospitalists in Colorectal Surgery

Abstract: Surgical comanagement intervention was associated with a decrease in transfers to the ICU after rapid response team call, LOS, medical consultants, and the cost of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 38 publications
1
27
0
Order By: Relevance
“…To our knowledge, this is one of the largest studies evaluating the benefits of SCM over 5.8 years. Similar to our prior studies on this SCM model of care, 5,7 other studies have reported a decrease in medical complications, 8-10 LOS, [11][12][13] and cost of care 14 with SCM.…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge, this is one of the largest studies evaluating the benefits of SCM over 5.8 years. Similar to our prior studies on this SCM model of care, 5,7 other studies have reported a decrease in medical complications, 8-10 LOS, [11][12][13] and cost of care 14 with SCM.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the foregoing, some studies failed to nd decreased mortality in comanaged patients. [8][9][10][11][12][13] In contrast to our patient population, which by design was older (mean age 81.4) and with signi cant comorbidity, these studies tended to have patients that were younger, with fewer comorbid conditions, and were largely undergoing elective surgeries. This dichotomy was commented on by Siegal in noting that two roughly simultaneous studies involving the same hospitalists and orthopedic surgeons found contrasting patient outcomes, as one study focused on healthier elective arthroplasty patients and the other on hip fracture patients who were older, more comorbid, and at higher risk for complications.…”
Section: Discussionmentioning
confidence: 99%
“…This differs from ndings in other comanagement studies. [6][7][8]12,13,15,19 Interestingly, ndings of decreased LOS and decreased mortality were largely mutually exclusive. Comanagement programs which were associated with decreased LOS tended to have patients who were younger and who were undergoing elective surgeries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported ICU admission rates in AMU care. One study on a surgical co-management model, which mainly focused on patients that required surgery, found a signi cant reduction in the ICU admission rate in the hospitalist group [35], compared to the non-hospitalist group. Other studies have reported no signi cant difference the ICU admission rates between the two types of care [36][37][38].…”
Section: Discussionmentioning
confidence: 99%